Souvenir Consumption in Tourism Industry - Liu, Shuang (2011)
The aim of the dissertation is to provide managerial implications on how to develop effective marketing strategy of souvenir products in China’s souvenir market through comparative evaluation of the souvenir consumption on the basis of case studies in souvenir market in China, the United States and the United Kingdom. By using z test which is useful in determining data frequencies, the findings suggest that the product assortment information indicates that tourists are interested in buying arts and crafts souvenirs when they travel to China comparing to travelling in USA/UK. Internal motivator of ‘adventure’ and external motivator of ‘cultural attractiveness’ explain that tourists are highly motivated by the newness and culture property of China as an attractive destination that participants’ desire to adventure the destinations which they have never been before and the long-inherited culture of China that attracted them to tour China. The motivation of being adventurous and cultural attractiveness also builds the foundation of investigating the association with the attitude on souvenir purchase behaviour of the tourists. Three product attributes have been rated relatively higher comparing to other attributes: ‘creative, novelty and unique’, ‘product quality’, and ‘aesthetic and craftsmanship’. Store employees’ service is found to be the store attribute appears to be of higher significance comparing to that of the context of travelling to USA/UK.